Case Report: Bilateral symmetrical primary kaposiform hemangioendothelioma of the femur - Qiu, Tong; Lan, Yuru; Zhou, Jiangyuan; Yang, Kaiying; Gong, Xue; Zhang, Zixin; Chen, Siyuan; Ji, Yi (Frontiers in Pediatrics, 2022)
Kaposiform Hemangioendothelioma (KHE) is a kind of rare borderline vascular tumor which usually presents as a mass of skin or deep soft tissue. We report a unique case of an 8-year-old KHE patient with bilateral symmetrical sites involving both femurs. The laboratory, radiographic, and pathological findings of the patient were minutely described. During the six-month follow-up, the symptoms of pain and dysfunction of this patient were relieved. This study was aiming to arouse clinicians' concern for symmetrical sites of KHE patients.